Evaluating clinical and laboratory effects of ozone in non-surgical periodontal treatment: a randomized controlled trial - Seydanur Dengizek, Eltas; Serkan, Dundar; Abubekir, Eltas; Aysun Bay, Karabulut; Onder, Otlu; Arife, Cicek (Univ Sao Paulo Fac Odontologia Bauru, 2019)
Objective: This study aims to evaluate the clinical and biochemical (oxidative stress and pro-inflammatory mediators) effects of the gaseous ozone use accompanied by scaling and root planning (SRP) in periodontal treatment. Material and Methods: The study population consisted of 40 patients with chronic periodontitis (CP) randomly sorted into two groups of 20. The experimental group received SRP plus 3 watts gaseous ozone in two separate applications five days apart, whereas the control group received SRP plus placebo. Clinical periodontal parameters were assayed and saliva samples were taken before the initial and one month after the second treatment. Periodontal examination assessed plaque index (PI), gingival index (GI), probing depth, and clinical attachment level (CAL). Total antioxidant status (TAS), total oxidant status (TOS), nitric oxide (NO), 8-hydroxy-2'-deoxyguanosine (8-OHdG), myeloperoxidase (MPO), glutathione (GSH), malondialdehyde (MDA), and transforming growth factor-beta (TGF-beta) levels were evaluated from saliva samples. Results: Changes following treatment in PI, GI, probing depth, and CAL scores were similar for both groups (p>0.05). Of note, TGF-beta levels were observed to be higher in the treatment group than in controls (p<0.05). Changes in 8-OHdG, TAS, TOS, NO, MPO, GSH and MDA levels, however, were not significantly different between groups (p>0.05). Conclusion: The findings of this study indicate that SRP plus gaseous ozone versus SRP alone does not correlate to a significant improvement in periodontal recovery.
Keywords: Chronic periodontitis; Inflammation; Ozone; Periodontal treatment; TGF-beta